2013
DOI: 10.1016/j.cej.2013.07.048
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of catechin and epicatechin from sago waste effluent: Study of kinetic and binary adsorption isotherm studies

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues.Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited. Recovery of catechin and epicatechin from sago waste effluent. Supercritical CO 2 desorption of catechin and epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 30 publications
(47 reference statements)
2
6
0
2
Order By: Relevance
“…The failure of the pseudo‐first‐order model in correlating adsorption kinetic experimental data is due to the theoretical interpretations of this equation. In pseudo‐first order it is based on the common assumption that the overall sorption process is controlled by the rate of adsorption/desorption processes which is seen as a chemical reaction on the surface of adsorbent . However in many cases, the rate of diffusion of solute into interior of the adsorbent also controls the adsorption mechanism and this phenomenon is not captured by the pseudo‐first‐order model .…”
Section: Resultsmentioning
confidence: 99%
“…The failure of the pseudo‐first‐order model in correlating adsorption kinetic experimental data is due to the theoretical interpretations of this equation. In pseudo‐first order it is based on the common assumption that the overall sorption process is controlled by the rate of adsorption/desorption processes which is seen as a chemical reaction on the surface of adsorbent . However in many cases, the rate of diffusion of solute into interior of the adsorbent also controls the adsorption mechanism and this phenomenon is not captured by the pseudo‐first‐order model .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported that the value of k 2 in the pseudo-secondorder model depended on the experimental conditions such as initial concentration, solvent volume, pH in a solution, temperature, and agitation speed (Sen Gupta and Bhattacharyya, 2011;Zhang et al, 2016). A lower k 2 value implies that a longer time is required to reach equilibrium (Sen Gupta and Bhattacharyya, 2011;Soetaredio et al, 2013). In this study, the values of k 2 using Lig and Lig800 were 0.06 and 0.09 g/mg/h, respectively, indicating that the time to reach the adsorption equilibrium did not differ between them under our experimental conditions.…”
Section: Effect Of Contact Time On the Adsorption Of Cd(ii)mentioning
confidence: 99%
“…Warna alami pati sagu berkontribusi terhadap peningkatan nilai a* egg roll. Umumnya pada proses ekstraksi pati sagu, endapan pati mengalami perubahan warna menjadi merah kecoklatan karena reaksi browning dari komponen fenolik yang terdapat di dalam vakuola dan dipicu oleh enzim Polifenol Oksidase atau PPO yang terdapat dalam plastid serta berkaitan dengan aktivitas enzim fenolase dengan komponen DLepicatechin dan D-catechin (Edi et al, 2013). Komponen tersebut sukar dihilangkan selama proses ekstraksi.…”
Section: Hasil Dan Pembahasan Warna Dan Tekstur Egg Rollunclassified
“…Makin tinggi konsentrasi pati sagu yang ditambahkan, warna kuning yang dihasilkan pada egg roll semakin berkurang. Hal ini kemungkinan disebabkan oleh warna alami pati sagu yang digunakan yaitu berwarna kemerahan yang disebabkan oleh reaksi reaksi browning enzimatis dari komponen fenolik yang dipicu oleh enzim PPO (Edi et al, 2013). dipengaruhi oleh kandungan kadar air dan karbohidrat pada pati sagu yang lebih tinggi.…”
Section: Hasil Dan Pembahasan Warna Dan Tekstur Egg Rollunclassified